2020
DOI: 10.1161/jaha.119.015515
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase‐Type Plasminogen Activator Receptor and High‐Sensitivity Troponin Levels Predict Outcomes in Nonobstructive Coronary Artery Disease

Abstract: Background Multiple biomarkers have been independently and additively associated with major adverse cardiovascular events in patients with coronary artery disease. We investigated the prognostic value of suPAR (soluble urokinase‐type plasminogen activator receptor) and hsTnI (high‐sensitivity troponin I) levels in symptomatic patients with no obstructive coronary artery disease. We hypothesized that high levels of these biomarkers will be associated with the risk of future adverse outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…OMCE incidence was reported as a study endpoint in three studies 11,13,15 . Fixed‐effects modelling showed that there was no substantial heterogeneity across these trials (I 2 = 9.8%; p = 0.330).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OMCE incidence was reported as a study endpoint in three studies 11,13,15 . Fixed‐effects modelling showed that there was no substantial heterogeneity across these trials (I 2 = 9.8%; p = 0.330).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies provided all‐cause mortality rates 10–17 . The degree of heterogeneity for this outcome was found to be very high (I 2 = 96.0%; p = 0.000).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained in the American study, in which most NOCAD patients had no increase in CRP [ 61 ]. Nevertheless, several studies showed that 30–55% of NOCAD patients demonstrated a substantial increase in CRP levels [ 62 , 63 , 64 ], although CRP levels did not correlate with increased mortality rates [ 64 , 65 ]. Interestingly, higher CRP levels were also reported in patients with arterial hypertension [ 66 ] and endothelial dysfunction [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Raised troponin levels in symptomatic patients are a substantial predictor of MACE [ 65 ]. Interestingly, patients with NOCAD who presented a significant increase in troponin due to a specific non-myocardial cause were at the same risk of death and MACE as patients with OCAD and elevated troponins during the 1-year follow-up [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Moreover, multiple studies have found increasing suPAR values to be prognostic for adverse events and mortality in patients with confirmed or suspected cardiovascular disease. 6,7,[36][37][38][39] To the extent of the authors' knowledge, only one study has investigated suPAR's prognostic ability in relation to cardiac surgery and demonstrated that increasing preoperative levels of suPAR were associated with higher risk of postoperative complications and 30-day mortality. 20 However, the study exclusively comprised patients with aortic stenosis for aortic valve replacement.…”
Section: Discussionmentioning
confidence: 99%